ANALISIS KOMPARASI FILSAFAT ILMU DAN ILMU FILSAFAT SERTA IMPLIKASINYA TERHADAP PENDIDIKAN MODERN - S., Sumarni; Sartika; Satria, Rama; Ibrahim, Duski; Syarnubi (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2023)
The aim of this research is to examine the comparison or difference between philosophy of science and philosophy of science and its implications for the development of education today. The method used in this research is library research. This research data collection used primary and secondary data sources. In analyzing the data, the author uses analytical descriptive data analysis techniques. Namely, data related to the theme being researched is collected and classified, then described and finally concluded. The result of this research is that philosophy can stand in the middle of the branches of science as a controller and director for its implementation. The following are several philosophical schools that have greatly contributed to the development of education today, namely progressivism (the implications are linked to the curriculum, so the curriculum must be open, adapted to local needs and centered on experience); essentialism (the implication is that the learning process needs to pay attention to the psychology and skills of students), and reconstructionism (the implication is that schools must direct change (the reconstruction of the current social order. As technology progresses over time, education must keep pace with this progress)